(untitled) (Canadian Medical Education Journal, 2013)
Resident duty hours have become an increasingly debated topic in post-graduate medical education. Work-hour restrictions have been implemented for first-year residents in the US and more recently for all residents in Quebec. Current and future work-hour rules affect a variety of stakeholders: government, hospitals, residency training programs, patients, and most of all residents. In this article, we hope to examine the issue from a Canadian perspective and delineate some of the reasons why changing the current call structure may have potentially deleterious effects to all those concerned.